The sea, the sea - Murdoch, Iris (London : Vintage, 1999)
When Charles Arrowby retires from his glittering career in the London theatre, he buys a remote house on the rocks by the sea. He hopes to escape from his tumultuous love affairs but unexpectedly bumps into his childhood sweetheart and sets his heart on destroying her marriage. His equilibrium is further disturbed when his friends all decide to come and keep him company and Charles finds his seaside idyll severely threatened by his obsessions.
Winner of The Booker Prize.
Keywords: Solitude -- Fiction